Sieving Effect of Agarose on Quasi-2D Silver Pattern Electroformation : A Pinning-Depinning-like Transition Resulting from Gelled Silver Plating Solutions - Pasquale, Miguel Ángel (2004)
New features of silver patterns grown in quasi-2D electrochemical cells of parallel plate cathode/anode design utilizing sol and gel aqueous silver plating solutions are reported. Morphology transitions in the silver growth patterns that depend on the composition of plating solutions are observed. These transitions are explained by both a sieving effect due to the presence of agarose and the change in the relative contribution of diffusion and advection to the mass-transport-controlled electrochemical process. Characteristic scaling lengths from growth patterns are related to both the gel structure and the geometry of electrodeposits. Gels consist of a percolated network of gel and randomly distributed colloidal particles, their size and velocity being represented by hyperbolic distribution functions. For silver plating gels a pinning-depinning transition in growth patterns is also observed. From the dynamic scaling analysis of growth pattern 2D profiles, the critical growth and roughness exponent as well as the characteristic lengths of the environment were evaluated. Values of these exponents approach those predicted either by the Kardar, Parisi, and Zhang (KPZ) deterministic equation, or by the cellular automata lattice model that has been proposed for the dynamics of a driven interface in a medium with random pinning forces.